Enhancing the Role of Modern Technologies in the Museum Display for Children: A case study of the Abu Bakr Gallery at Sharjah Museum of Islamic Civilization - AlObeidli, Entisar; Jamhawi, Monther; Hussien, Aseel (Al-Adab Journal, 2023)
Sharjah has always been committed to spreading culture and education through various cultural platforms, of which museums are the most significant. Museums serve as historical, heritage, and learning sites for various segments of society, where science, arts, and heritage are displayed. The Sharjah Museum of Islamic Civilization is one of the most striking cultural landmarks in the Emirate of Sharjah. Through educational and cultural programs, events, exhibitions, and activities, it preserves and displays collections from the Islamic world to promote knowledge and understanding of Islamic history, sciences arts and culture. The museums displays are divided amongst six galleries, including the Abu Bakr Islamic Faith gallery. This gallery features the pillars of Islam, manuscripts, the art of calligraphy, as well as models of mosques’ architecture. The existing interpretation, however, could be simplified to provide a more enticing and interactive experience for children. The aim of this study is to examine the current museum display, in this gallery, to identify the impact of modern technologies on the interaction and participation of children aged 8-12 years with the exhibits. To address the research questions and fulfill the goals of the study, data were gathered using references and books on various types of technologies and surveys were distributed to museum visitors (families and teachers as well as children. In addition, interviews were conducted with museum officials and notes recorded by the researcher as a museum curator. Additionally, examples of display methods and the use of technology in children’s museums were analyzed. Results were derived after analyzing the data in relation to the current display and factors of visitor attraction. For the current display content to be attractive to the target group, it must be updated according to its educational value. This is in addition to modern technology currently being used in various galleries, such as touch screens, virtual reality, and augmented reality. It is also important to create an environment where learning and interaction can be integrated in the museum display to make it appealing to children.